Sensory Preferences of Adults with Substance Use Disorder: Do They Correspond with Substance of Choice?. (2nd January 2023) - Gardner, Jennifer; Kitzinger, Robert H.; Bundesen-Magier, Maya; Abdallah, Kerri; Cervantes, Manny; Armada, Alexa Rae
Abstract: The purpose of this study was to describe sensory preferences of adults with substance use disorder using Adolescent/Adult Sensory Profile (A/ASP), and to explore relationships between sensory preferences and substance of preference. Participants ( N = 57) completed a survey and A/ASP. Majority scored "similar to most" in all four quadrants of A/ASP when compared to the normative samples, despite previous research indicating differences in sensory preferences for this population. Participants reported alcohol, heroin, and marijuana as most preferred substances. There were no statistically significant associations between sensory preferences and substance preferences within substance groups, with p -values ranging from .067 to .904. Occupational therapists can use results of A/ASP to help clients develop alternative substance-free recovery.